In-vitro Anti-tuberculosis Activity and Phytochemical Screening of Lantana (Lantana camara L.) Flower - Ferna Indrayani; Reski Yalatri Wirastuty (Pharmacy Faculty, Universitas Muhammadiyah Purwokerto, 2021)
This study aimed to determine the quality of raw materials, screen the phytochemicals, and evaluate the anti-tuberculosis activity of Lantana (Lantana camara L.) flower extract. The method used was direct observation in the laboratory. Lantana flower were processed into crude drugs and then extracted using 70% ethanol solvent. The extract obtained was evaluated for phytochemical screening and anti-tuberculosis activity assay. The in-vitro anti-tuberculosis activity assay was carried out using the Lowenstein-Jensen method. The results showed that the ethanolic extract of the Lantana flower was thick, dark brown with an aromatic odour and tasteless. The ethanolic extract of the Lantana flower showed a specific gravity of 1.0028 g/ml, the ethanol-soluble extractable of 1.15%, water-soluble extractable of 1.187%, the loss on drying of 8.21%, and total ash content of 9.40%. It contained chemical compounds such as alkaloids, flavonoids, tannins, saponins, steroids, and glycosides. The in-vitro results showed that extract at concentrations of 25, 50, and 100 µg/ml showed no colonies on the media from the 1st to the 6th week. Hence can be reported as susceptible. It can be concluded that the ethanol extract of the Lantana flower contains chemical compounds that potentially as anti-tuberculosis.